A master’s vocal recital analyzing the historical and stylistic aspects of works by George Frideric Handel, Wolfgang Amadeus Mozart, Franz Schubert, Vincenzo Bellini, Giuseppe Verdi, Gaetano Donizetti, Reynaldo Hahn, and Michael Head - Tackett, Joshua Lucas (Kansas State University, 2014)
The songs presented in this report are works I performed in my Master’s Recital on March 30, 2014. This report will take an in-depth analysis at the selected composers’ life and styles of writing and the works they created. The scores studied in this report include: “Thus saith the Lord: But who may abide” from George Frideric Handel’s Messiah, “Soave sia il vento” from Wolfgang Amadeus Mozart’s Cosí fan Tutte, “Liebesbotschaft,” “Ihr Bild,” and “Das Fischermädchen” from Franz Schubert’s Schwanengesang, Vincenzo Bellini’s “Vaga luna che inargenti,” Giuseppe Verdi’s “Il Poveretto,” Gaetano Donizetti’s “Che vuoi di più,” Reynaldo Hahn’s “Á Chloris,” “Si mes vers avaient des ailes,” and “L’Heure Exquise” from Chanson grises, and “Ships of Arcady,” “Beloved,” “A Blackbird Singing,” and “Nocturne” from Michael Head’s Over the Rim of the Moon.
Keywords: Michael Head; Bel Canto; Reynaldo Hahn; Music (0413)